VACUUM THERAPY IN DIABETIC FOOT SURGERY - Mazhit A. Nartaylakov; Marat R. Garaev; Vadim D. Dorofeyev; Bulat R. Giniatullin; Vitaliy A. Zavarukhin; Ilshat R. Akhmetshin; Artur K. Burkhanov; Tatyana P. Gvozdik; Rail R. Sharipov (Креативная хирургия и онкология, 2017)
Introduction. Various techniques of controllable level of negative pressure are presently a trending treatment of purulent-necrotic wounds. Despite the widespread view in the literature about the obvious benefits of this method, there are still no extensive research, free from commercial interests. In this context, the main objective of this study was to evaluate early results of vacuum therapy in complex treatment of purulonecrotic wound. Materials and methods. The work includes data of multi-dimensional follow-up study with non-parallel (historical) control. Retrospective study included analysis of case histories in the period 2010 - 2012 (140 patients), prospective study was to analyse the effectiveness of vacuum therapy in complex treatment of purulent diseases in patients hospitalized in purulent surgery department at Republic Clinical Hospital. G.G. Kuvatov UFA) during the period 2012-2016 (142 patients). Results. The findings show that the application of negative pressure treatment method in complex treatment of patients with infected wounds of soft tissues is indicated in cases where there has been a slowing of wounds cleansing and reparative processes - the method allows to reduce number of bandaging for a patient, the timing of wound cleansing and accelerate the transition to the phase of plastic closure of the wound. Conclusions. To reduce the risk of bleeding on vacuum therapy, following extensive surgical interventions, it is optimal to comply with temporary pause between surgical effect on wound and installing of apparatus NPWT (8-16 hours). The best effect in the treatment of wounds can be achieved when applying the following NPWT mode: the first 24 hours after the beginning of vacuum therapy - a constant level of negative pressure at 100-140 mm Hg.; second day and further - intermittent level of negative pressure with alternating modes at 60-75 mm Hg. - 5 minutes and 120-130 mm Hg. -5 minutes.